The Ability to Use the Conjunctions "ZHIYOU...CAI" and "ZHIYAO...JIU" by fourth-semester students of STBA-PIA Medan. - Wijaya, Silvia; karina, Karina (Journal of Language, Literature and Teaching, 2024)
This study aims to analyze the ability of fourth-semester or Second year students of STBA-PIA Medan to use the Chinese conjunctions “zhiyou……cai” and “zhiyao……jiu” and to identify the factors influencing this ability. The research uses an integrative research design, combining quantitative and qualitative methods to complement each other. Data were collected through tests, while the factors influencing ability were analyzed through interviews. The data analysis results show that the fourth-semester students of the Chinese Literature program at STBA-PIA Medan demonstrated a high level of proficiency, with an average score of 87. The median score was 90, the mode was 95, and the standard deviation was 13. The factors influencing the students’ ability to use the conjunctions “zhiyou……cai” and “zhiyao……jiu” consist of four factors: (1) motivation, which includes internal and external motivation, short-term and long-term motivation, and integrative and instrumental motivation, (2) formal instruction, (3) first language influence, and (4) environmental factors, including formal and informal environments.Keywords: Comprehension, Usage, Conjunctions, “zhiyou……cai”, “zhiyao……jiu”.